The health of working dogs in conservation in Africa - Earnshaw, Nicola; Anderson, Neil; Mackay, Jill; Parker, Megan (Frontiers in Veterinary Science, 2023)
Dogs are increasingly being employed for conservation purposes worldwide. In Africa, they work in challenging environments with unique health risks which have not been investigated until now. To understand the challenges, semi-structured interviews were conducted with participants from 14 organisations that used working dogs in their conservation programmes. Thematic analysis of the interview data generated five themes and recommendations were made based on these themes. Three affective themes influenced how participants responded to the challenges associated with having a successful conservation dog programme. A strong handler-dog attachment, proficient handler training and the acknowledgement of the challenging environment were pivotal to maintaining dog health. Two themes related to the difficulties in managing these programmes and how veterinary support interacts with the management choices being made. To have healthy conservation dogs, current and future programmes should focus on fostering the handler-dog relationship and provide continuous handler training. The management of conservation dogs' health should adopt an evidence-based approach. Future research should focus on areas where the evidence base is lacking, particularly in the areas of prevention and treatment of African canine trypanosomiasis. Programmes should develop a good working relationship with a veterinarian that has access to evidence-based veterinary medical information.